Relational marketing throughout the history of commercial exchange: Blind spots in marketing's origin story. Issue 3 (2nd July 2020) - Edwards, Chase J.; Baker, Brent L.
Abstract: Although marketing is commonly theorized to have originated at the dawn of exchange itself, few scholarly articles explore the history of marketing beyond this cursory recitation of the commonly accepted origin story of the field. The evolution of complex commercial exchange is presented as a natural outgrowth of the development of human society as opposed to the willful and intentional efforts of early merchants. Using disparate and archaic sources, this article synthesizes historical accounts and archival information to show that entrepreneurs have always practiced relational marketing from prehistoric eras and continued to do so throughout pre-industrial and post-industrial eras when the bulk of the literature claims that the scale of modern production rendered relational marketing ineffective and nearly obsolete. In doing so, we add to the virtually non-existent literature documenting entrepreneurial marketing in the early, pre-industrial history of commerce.